Strontium and bisphosphonate coated iron foam scaffolds for osteoporotic fracture defect healing. (March 2018) - Ray, Seemun; Thormann, Ulrich; Eichelroth, Marlen; Budak, Matthäus; Biehl, Christoph; Rupp, Markus; Sommer, Ursula; El Khassawna, Thaqif; Alagboso, Francisca I.; Kampschulte, Marian; Rohnke, Marcus; Henß, Anja; et al.
Abstract: The purpose of this work was to investigate new bone formation in macroporous iron foams coated with strontium (FeSr) or bisphosphonate (FeBiP) compared to plain iron foam (Fe) and empty defect in a critical size metaphyseal bone defect model in ovariectomized rats. 60 female rats were subjected to bilateral ovariectomy and multi-deficient diet for 3 months. A 4 mm wedge shaped metaphyseal osteotomy was created, fixed with a mini-plate and subsequently filled with Fe, FeSr, FeBiP or left empty. After 6 weeks, μCt analysis revealed a statistically significant increased bone formation at the implant interface in FeSr compared to FeBiP (p = 0.035) and Fe (p = 0.002), respectively. Increased mineralized tissue was also seen within the pores in FeSr (p = 0.023) compared to Fe. Histomorphometry revealed significantly increased bone formation at the implant interface in FeSr (p < 0.001) and FeBiP (p = 0.006) compared to plain Fe with increased osteoblast and decreased osteoclast activity in combination with increased BMP2 and decreased RANKL/OPG in immunohistochemistry. ToF-SIMS analysis showed overlapping Ca signals with Fe for both FeSr and FeBiP thereby indicating tissue in-growth into the scaffolds. In conclusion, iron foam with strontium or bisphosphonate coating are of further interest in metaphyseal fracture defects in osteopenic bone.